Implementation of Customer Relationship Management (CRM) inAgribusiness to Enhance Students' Competency: A Participatory Action Research at SMKN PP Lembang - Yoga, Titan Parama; Alamsyah, Nur; Bilqist, Dhiya Waffa Putriana; Nazahah, Niswah Kaifa (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aimed to enhance students' understanding of Customer Relationship Management (CRM) in agribusiness at SMKN PP Lembang using the Asset-Based Community Development (ABCD) approach. The program involved 120 grade XII students and included a pre-test, material presentation, discussions, and a post-test to evaluate knowledge improvement. The pre-test average score was 58%, while the post-test average rose to 85%, showing a 27% improvement in comprehension. The most notable improvements were seen in topics such as CRM tools, customer segmentation, and digital marketing strategies. The findings highlight the effectiveness of integrating CRM education into vocational training to equip students with practical business skills and decision-making capabilities.